Microsoft Office Access 2003, Illustrated Complete - Friedrichsen, Lisa (Cengage Learning, Inc, 2006)
Part of the Illustrated series, this text offers a visual, flexible way to build Microsoft Access 2003 skills. Basic to advanced topics are presented in a clean, easy-to-follow layout that combines action steps on the left-hand page and colorful, large illustrations on the right. With this succinct approach, students learn by following the clear instructions provided while allowing freedom in exploration within Access 2003